Great philosophical objections to artificial intelligence : the history and legacy of the AI wars - Dietrich, Eric; Fields, Chris; Sullins, John P.; Van Heuveln, Bram; Zebrowski, Robin (London, England : Zed Books, 2021)
"This book surveys the most famous philosophical arguments against building a machine with human-level intelligence. From claims and counter-claims about the ability to implement consciousness, rationality, and meaning to arguments about cognitive architecture, it presents a vivid history of the clash between philosophy and AI. With introductions to each war and further readings, this forward-looking book is packed with fresh insights and supporting material"--
Part I. The AI Wars, 1950 to 2000: Gödel and a foundational objection to AI -- How would we know if a computer was intelligent? The Turing Test is not the answer -- How computer science saved the mind -- Implementing an intelligence -- The strange case of the missing meaning: can computers think about things? -- What is relevant to what? The frame problem -- Part II. Beyond the Al Wars: issues for today: What about consciousness? -- Ethical issues surrounding AI applications --
Includes bibliographical references (pages 275-298) and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Artificial intelligence -- Philosophy; Philosophy; Electronic books